2001
DOI: 10.1017/s0025315401004118
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of crustaceans from 13 sheltered sandy beaches along São Sebastião Channel, south-eastern Brazil

Abstract: The crustacean species composition in the intertidal zones of 13 sheltered unconsolidated marine beaches in south-eastern Brazil is described. Fifty-three crustacean species were collected, adding 46 species to the total reported by previous studies in the same region. Decapods dominated the community, in contrast to exposed sandy beaches where peracarids normally predominate. The species were distributed irregularly among the beaches. Richness varied markedly among sites, and was positively related to a combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
7

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 10 publications
1
22
0
7
Order By: Relevance
“…Among crustaceans, most of these studies have been conducted in intertidal and shallow subtidal species from hard bottom environments (Jensen & Armstrong, 1991;Nucci et al, 2001;Caillaux & Stotz, 2003;Takeda et al, 2004;Pallas et al, 2006;Viegas et al, 2007). The distribution and conditions explaining the abundance of crustaceans from soft bottom habitats and environments deeper than 10 m are much less known.…”
Section: Introductionmentioning
confidence: 99%
“…Among crustaceans, most of these studies have been conducted in intertidal and shallow subtidal species from hard bottom environments (Jensen & Armstrong, 1991;Nucci et al, 2001;Caillaux & Stotz, 2003;Takeda et al, 2004;Pallas et al, 2006;Viegas et al, 2007). The distribution and conditions explaining the abundance of crustaceans from soft bottom habitats and environments deeper than 10 m are much less known.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Veloso and Cardoso (2001) show that the abundance of the communities was also not related to any physical parameter and these authors suggested that certain biotic factors, such as food source, recruitment, predation and competition, are responsible for the differences in macrofaunal densities between beaches. In addition, Nucci et al (2001) have demonstrated a relationship between environmental heterogeneity and species richness.…”
Section: Discussionmentioning
confidence: 99%
“…Kihara & Rocha, 1993-Callinectes danae Smith, 1869Lacerda, 1981Mossolin, 1994;Caprara & Freitas, 1996;Lowenthal et al 1996;Nucci, 1998;Genofre et al 2000;Nucci et al 2001;Turra & Leite, 2005;Padovanni, 2009-Callinectes ornatus Ordway, 1863Nucci, 1998Nucci et al 2001;Gorni & Weber, 2004-Clibanarius antillensis Stimpson, 1862Garcia, 1979Brossi-Garcia & Hebling, 1983;Arantes & Leite, 1991bJacobi, 1992;Leite et al 1995Leite et al , 1996Nalesso et al 1995;, 20022004Turra et al , 1999Turra et al , 2000Barata et al 1996;Castelo-Branco et al 1996;Jacobucci & Leite, 1996;Turra & Denadai, 2001, 2002, 2004Souza, 2003;Turra, 2003Turra, , 2004Turra, , 2005 Clibanarius sclopetarius (Herbst,1796) Brossi- Garcia, 1987;Arantes & Leite, 1991bJacobi, 1992;Leite et al 1995...…”
Section: Táxon Superior Espéciementioning
confidence: 99%
“…Arantes & Leite, 1991a;, 1997Barata, 1996;Barata et al 1996 Epialtus brasiliensis Dana,1852 Duarte, 1980b;Nalesso et al 1995;Duarte & Nalesso, 1996;Morgado & Tanaka, 2001 Epialtus sp. Milanelli, 2003-Eriphia gonagra (Fabricius, 1781) Santos & Bueno, 2001Turra & Leite, 2005-Eurypanopeus abbreviatus (Stimpson, 1860) Milanelli, 2003-Hexapanopeus paulensis Rathbun, 1930Duarte, 1980bNalesso et al 1995;Duarte & Nalesso, 1996-Hexapanopeus schmitti Rathbun, 1930Duarte, 1980bDuarte & Nalesso, 1996;Nucci, 1998;Nucci et al 2001;Amaral et al 2003-Hippolyte curacaoensis Schmitt, 1924Christoffersen, 1980-Lepidopa sp. Ditadi, 1982b-Leptalpheus axianassae Dworschak & Coelho, 1999Dworschak & Coelho, 1999-Megalobrachium soriatum (Say, 1818) Duarte, 1980bMorgado, 1980b;Nalesso et al 1995;Duarte & Nalesso, 1996;Morgado & Tanaka, 2001-Menippe nodifrons Stimpson, 1859Duarte, 1980bNalesso et al 1995;…”
Section: Táxon Superior Espéciementioning
confidence: 99%
See 1 more Smart Citation